Tropical cyclone-induced cold wakes in the northeast Indian Ocean. Issue 3 (24th February 2022) - Kuttippurath, J.; Akhila, R. S.; Martin, M. V.; Girishkumar, M. S.; Mohapatra, M.; Balan Sarojini, B.; Mogensen, K.; Sunanda, N.; Chakraborty, A.
Abstract : The physical processes during cyclone passage over the ocean. Air–sea interactions. Abstract : We present a detailed long-term (1982–2020) analysis of cyclone-induced surface cooling ( i.e., cold wake) in the northeast Indian Ocean, which hosts about 6% of the annual tropical cyclones in the world. Here, the analysis is performed for 92 cyclones that triggered significant cooling at the sea surface in two different seasons: the post and pre-monsoons. It is found that these cyclones generally cool the sea surface from 0.5 °C to 4.81 °C after their passage; depending on the cyclones. The pre-monsoon cyclones show stronger cooling, but the post-monsoon cyclones exhibit a longer duration of cooling and recovery time. Slow-moving cyclones (translational speed less than 3 m s −1 ) impose more stress on the ocean surface and produce stronger cooling, due to upwelling and associated vertical mixing. Furthermore, the cyclones that occurred during La Niña years show relatively more intensity than those in the El Niño years. Since the sea surface temperature (SST) drop impedes cyclones from further intensification, our study gives new insights into the cyclone intensity in the Bay of Bengal. Additionally, the range of surface cooling derived from this analysis can help coupled numerical models to improve the forecast of intensity and landfall of cyclones, which can save millions of lives and the coastal ecosystem.